2022
DOI: 10.21203/rs.3.rs-2418801/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Variability in soil quality among smallholder macadamia farms in Malawi

Abstract: Declining soil fertility limits smallholder macadamia productivity in Malawi. In order to reverse this trend, it is essential to apply organic and inorganic fertilisers in an efficient and effective manner. Yet, fertiliser recommendations for smallholder macadamia (Macadamia integrifolia) production in Malawi are not site-specific. Nutrient imbalances can occur if fertilisers are applied without a clear understanding of whether they are required or not. This may lead to yield losses, unnecessary costs, and oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…The predominant reason driving consumption is the nutritional benefits of nuts. For example, findings from a study conducted by Zuza [90] revealed that a significant majority, approximately 61% out of 144 participants, consumed macadamia nuts primarily for their health and dietary value. This emphasizes the nuts' potential to nutritionally complement the country's cereal-heavy diets.…”
Section: Consumption Of Macadamia Nuts In Malawimentioning
confidence: 99%
“…The predominant reason driving consumption is the nutritional benefits of nuts. For example, findings from a study conducted by Zuza [90] revealed that a significant majority, approximately 61% out of 144 participants, consumed macadamia nuts primarily for their health and dietary value. This emphasizes the nuts' potential to nutritionally complement the country's cereal-heavy diets.…”
Section: Consumption Of Macadamia Nuts In Malawimentioning
confidence: 99%
“…Many also lack knowledge about the precise amount of fertilizer needed to optimize crop yields [20] , often leading to the over-application of chemical fertilizers, causing soil and environmental degradation [21] . Others have adhered to blanket fertilizer recommendations, which fail to account for the specific nutrient requirements of their own fields, resulting in stagnant or even declined yields [22,23] . Given these challenges, enhancing smallholders' capabilities to understand and adopt wellestablished technologies is key to Africa's sustainable agricultural development [24] .…”
Section: Introductionmentioning
confidence: 99%